TARIK MENARIK KEWENANGAN PEMERINTAH PUSAT DAN PEMERINTAH ACEH DALAM PENGESAHAN QANUN BENDERA DAN LAMBANG ACEH - Fadhil Ilhamsyah (Jurnal Public Policy, 2017)
This research examines the relationship of the authority of the Central Government and the Acehnese Government in endorsement Qanun flag and emblem of Aceh. This study uses qualitative methods, in which the source data is obtained with the technique of librarianship and in-depth interviews. From the results of this research show that the relation is the authority of the Central Government and the Acehnese Government in endorsement Qanun flag and emblem of Aceh going on and entwined on the authority, namely the supervision and attestation against Qanun. The Government of Aceh was given the authority to set a then the Qanun is evaluated by the Central Government to ensure that the Qanun has set are not contrary to the public interest, Qanun, and regulations legislation is higher. Keywords: Authority, Aceh flag and emblem